(untitled) (Altre Modernità, 2022)
This article proposes a reflection on the profound process of mutation that has taken place in university literature teaching in recent years, which has been affected by a massive recourse to digital and remote teaching. In particular, a marked acceleration of this mutation process due to the spread of the Covid-19 pandemic has been observed. The analysis, divided into two sections, using both a psycho-pedagogical and a didactic perspective, will see in the first part a reflection on the new forms of university literary teaching, with particular reference to the relationship between the changed cultural status of literature, remote teaching and digital natives taking into account the context of a post-modern society (Marone and Striano 2012). In the second part, the case study of a university course in English literature carried out through the instrument of the validated questionnaire will be analysed. The effectiveness of remote teaching will be tested on the responses of a representative sample of students aged between 20 and 23 years attending the second year of a basic degree course in languages. On the basis of the data collected, development hypotheses will be examined for new epistemic perspectives for the teaching of literary disciplines, with particular reference to foreign and English-speaking literatures.